Porous carbon supported calcium oxide for CO2 adsorption and separation of CO2/CH4. Issue 3 (28th January 2022) - Jonnalagadda, Madhavi; Ibrahim, Sobhy M.; Shair, Omar H. M.; Mutyala, Suresh
ABSTRACT: Calcium oxide incorporated porous carbon materials were synthesized by the impregnation method to study CO2 adsorption and separation of CO2 /CH4 . The X-ray diffraction, Raman analysis, N2 isotherms at 77 K, and SEM with EDX analysis were used to characterize synthesized materials. XRD and N2 isotherm results have confirmed that synthesized carbon has porosity, and EDX analysis has reported that the presence of CaO on porous carbon. 10CaO/porous carbon has shown 31 cm 3  g −1 of CO2 adsorption which was higher than bare porous carbon CO2 adsorption 17.5 cm 3  g −1 at 298 K, 1 bar. It was attributed to electrostatic interaction between CaO and CO2 . However, CH4 adsorption was decreased by a decrease in surface area. The selectivity of CO2 /CH4 was higher for 10CaO/porous carbon and the heat of CO2 adsorption was 36 KJ/mol at high adsorption of CO2 . Moreover, CO2 adsorption was the same in each adsorption cycle. GRAPHICAL ABSTRACT: UF0001